Exploring The Influence of Price and Service Quality on Customer Satisfaction: A Study of Maxim Ride-Hailing in Palembang - Indah, Ratu; Putri, Yulia Hamdaini; Yunita, Dessy (Teewan Journal Solutions, 2026)
This study aims to analyze the influence of price and service quality on consumer satisfaction in Maxim's ride-hailing service in Palembang City. The study used a quantitative approach with a non probability dampling technique through a purposive sampling method involving 100 active users of Maxim's ride hailing service. Data were collected through a questionnaire using a 5-point Likert scales distributed both online and offline. Data analysis was conducted using multiple linier regression to examine the influence of price and service quality on customer satisfaction. Competitive and transparant pricing plays an important role in increasinf consumer satisfaction, while the dimensions of service quality- tangible, reliability, responsiveness, assurance, and empathy- have a greater influence on overall satisfaction. This research is expected to contribute to the literature on the relationship between price, service qualty, and consumer satisfaction, particularly in the context of online transportation services. Practically, these findings provide recommendations for Maxim to maintain a balance between affordable pricing strategies and improved service quality to sustain consumer trust and competitiveness in the market.